Rheological behavior of SS316l gas atomized powder in bimodal particle size distribution in a composite binder system - Jamaludin, Khairur Rijal; Muhamad, N.; Amin, S. Y. M.; Ab. Rahman, M. N.; Murtadhahadi, Murtadhahadi (University of Malaya, 2008)
Rheological properties of the monomodal and bimodal MIM feedstock are presented in this paper. Coarse and fine SS316L gas atomized powders are mixed with PEG and PMMA to form a homogenous paste, which is termed as feedstock. The surface active agent used here is stearic acid. The bimodal powders are blended from 30 to 70 % of the coarse powder distribution. Results show that monomodal feedstock exhibits a higher viscosity over the bimodal feedstock at low shear rate. Binder separation is also likely to occur in the monomodal feedstock prepared with coarse powder especially at a high injection temperature. Furthermore, bimodal feedstock is less viscous than the monomodal feedstock but the particle size distribution has shown its influence on viscosity. The flow behavior index decreases when the temperature increases. The investigation also shows that the feedstock flow sensitivity depends on the fine powder distributions in the feedstock. Since all the feedstock demonstrates a good pseudo plastic behavior, it therefore is suitable to be injection molded.